Ethical framework for FACILITATE: a foundation for the return of clinical trial data to participants - Staunton, Ciara; Blom, Johanna M. C.; Mascalzoni, Deborah; , on behalf of the IMI FACILITATE Consortium (Frontiers in Medicine, 2024)
up to 125 words in a bullet point format)• This paper discusses the importance of return of clinical trial data to patients in the context of the FACILITATE project that aims to develop a participant -centric approach for the systematic return of individual clinical trial data.• It reflects on the need for an ethical framework to support the return of clinical trial data.• The discussion revolves around the developing FACILITATE ethical framework, specifically focusing on the ethical principles that form the foundation of the framework and guidance on how to implement those principles into practice.